Acute effect of intensity and volume during strength training on sensation of pleasure, rating of perceived exertion, and pain in trained men - Gustavo César Vasconcelos; Igor Damorim; Tony Santos; Dalton Lima-Junior; Leonardo Fortes (Termedia Publishing House, 2021)
Purpose The purposes of this study were: (a) to compare the sensation of pleasure, rating of perceived exertion (RPE), and pain in different volumes (volitional failure [VF] vs. fixed repetitions [FR]), equalizing the intensity; and (b) to compare the sensation of pleasure, RPE, and pain in different intensities (40%, 60%, and 80%) of one-repetition maximum (1RM), with equalization of training volume. Methods A total of 12 trained men (aged 24.9 ± 4.3 years) performed 3 sets of seated row, leg press 180°, and chest press at 3 different intensities (40%, 60%, and 80% 1RM) for both training strategies (VF vs. FR). Results There was a decrease in pleasure and an increase in RPE and pain in VF training sessions at intensities of 40% and 60% 1RM compared with FR. However, no difference was observed for the intensity of 80% 1RM for pleasure. A doseresponse effect was revealed in the comparison of intensities for pain and RPE. In turn, no effect was found for pleasure. Conclusions VF training sessions decreased responses regarding pleasure, as well as increased RPE and perceived pain for the intensities of 40% and 60% 1RM when compared with the same intensity in FR among trained men. Different intensities were not able to change the sensation of pleasure.